Pemanfaatan Bahan Pakan Alternatif Sumber Nabati dan Hewani untuk Meningkatkan Produktifitas dan Efisiensi Budidaya Unggas Di Kampung Unggas Teruwai - Purnamasari, Dwi Kusuma; Wiryawan, K.G.; Erwan, Erwan; Maslami, Vera; Klana, Jaya (Jurnal Gema Ngabdi, 2025)
Farmers’ lack of awareness about the various plant and animal based alternative feed ingredients for poultry is the basis and objective of community service activities in the Teruwai poultry. The activities were carried out in three stages: Stage I, which consisted of preparation through discussions and communication with the livestock group leader and several farmers; stage II, which consisted of distributing materials on various plant and animal based alternative feeds, their advantages and uses for poultry farming, as well as providing materials on one of the animal based ingredients, specifically BSF larvae, which farmers could request; and Stage III, which consisted of mentoring farmers in the cultivation of BSF larvae. The community service participants were groups of male and female poultry farmers and young men and women from the Teruwai poultry community, a total of 20 people. The community service activities were successfully implemented and managed, with the participation of 30 people, including farmers, poultry group, and young men and women from Teruwai poultry community service participants, as evidenced by the attendance rate, with exceed the target, discussion, and a desire to learn more, especially about BSF larvae. The activity continued with concrete actions to cultivate BSF larvae in group cages. The conclusion is that this community service activity generated increased knowledge, enthusiasm, and concrete actions on the part of leader and members of the poultry group in Teruwai Village